Teaching Public Service in the Digital Age: Collectively Building a Global Curriculum to Teach Digital-era Competencies to Public Managers - Eaves, David; Mergel, Ines; Clarke, Amanda; Fetter, Jordyn; Steinberg, Tom (Sage publications, 2026)
Public administration educators typically fail to incorporate evidence-based or even hypothesized guidance on the necessary digital competencies needed by public leaders and how they should be taught. Recognizing this gap, we apply participatory action research to derive eight competences and supporting teaching tools for digital government teachers. This involved convening focus groups of academics and practitioners to collect data, interviews, and participant observations. These data informed the development of a draft set of digital-era competencies for public leaders and provided a basis for debate and refinement in international focus groups. These competencies were then taught in prototype course settings and further developed and dissemination in the form of train-the-trainer materials and teaching information to over 200 professors from more than 50 countries. The eight high-level competencies emerged from this process. We suggest how to scale up training based on the experience of developing and teaching these competencies, focusing on the institutional and cultural barriers that must be overcome to modernize mainstream public administration education in the digital age. Lastly, we outline lessons learned from developing digital-era competencies to inform faculty and administrators of public affairs schools, as well as certification bodies.
Keywords: Digital government; Teaching; Curriculum development; digital competencies; train-the-trainer; participatory action research; public administration; fi=Julkisjohtaminen|en=Public Management|